ANALISIS KESULITAN GURU DALAM MENGEMBANGKAN MODUL AJAR PADA KURIKULUM MERDEKA DI SDN 17 PEKANBARU - Devi Aryani; Zaka Hadikusuma Ramadan (STKIP Subang, 2024)
Teaching modules are one of the important components of the Independent Curriculum. Teachers are given the freedom to develop teaching modules according to the characteristics of students. However, in reality teachers still experience difficulties in developing teaching modules. The aim of this research is to find out what difficulties teachers experience in developing teaching modules. This type of research is naturalistic inquiry with a qualitative approach. descriptive qualitative research. The data collected in this research was obtained from interviews and documentation. The source of this research is the principal, teachers of classes IV-A, I-B, I-D and IV-D at SD Negeri 17 Pekanbaru. The results of this research show that the difficulties experienced by teachers in developing teaching modules are 1) difficulties in determining the components of teaching modules, (2) difficulties in determining learning objectives, (3) difficulties in determining learning models and methods, 4) difficulties in presenting material and delivering material according to time allocation, 5) difficulties in determining assessments. The causes are due to less than optimal training, diverse characteristics of students, and limited time.